2010
DOI: 10.1530/eje-10-0818
|View full text |Cite
|
Sign up to set email alerts
|

GH and IGF1 levels are positively associated with musculotendinous collagen expression: experiments in acromegalic and GH deficiency patients

Abstract: Objective: Disproportionate growth of musculoskeletal tissue is a major cause of morbidity in both acromegalic (ACRO) and GH-deficient (GHD) patients. GH/IGF1 is likely to play an important role in the regulation of tendon and muscle collagen. We hypothesized that the local production of collagen is associated with the level of GH/IGF1. Design and methods: As primary outcomes, collagen mRNA expression and collagen protein fractional synthesis rate (FSR) were determined locally in skeletal muscle and tendon in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 57 publications
(61 reference statements)
1
47
0
Order By: Relevance
“…They found a tendency toward a smaller tendon collagen fibril area and a higher concentration of small collagen fibrils in acromegalic patients than in GH-deficient patients. This finding suggests that a chronically high level of GH/IGF1, with a concomitant increase in collagen expression and in absolute collagen synthesis, correlates with a smaller collagen fibril area in the tendon [17].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…They found a tendency toward a smaller tendon collagen fibril area and a higher concentration of small collagen fibrils in acromegalic patients than in GH-deficient patients. This finding suggests that a chronically high level of GH/IGF1, with a concomitant increase in collagen expression and in absolute collagen synthesis, correlates with a smaller collagen fibril area in the tendon [17].…”
Section: Discussionmentioning
confidence: 79%
“…A doubling of GH and IGF-I levels did not change the collagen fibril volume fraction, but it did affect the diameter distribution as it presented more small fibrils than in the control mice [16]. In the second study, Doessing et al found quantitative collagen morphology in the tendons of acromegaly patients [17]. They found a tendency toward a smaller tendon collagen fibril area and a higher concentration of small collagen fibrils in acromegalic patients than in GH-deficient patients.…”
Section: Discussionmentioning
confidence: 97%
“…In a study the collagen mRNA expression and collagen protein fractional synthesis rate (FSR) was evaluated locally, in muscles and tendons, by means of microdialysis technique, in acromegalics, relative to GH deficient patients 34 . A higher expression for collagen and IGF1 mRNA was found in acromegalics.…”
Section: Gh/igf-1 Systemmentioning
confidence: 99%
“…GH increases IGF-1 expression; acromegalic patients (who produce excess GH), for example, display a 2.9-fold increase in IGF-1 expression relative to GH-deficient patients. Musculotendinous collagen expression was elevated 1.7-fold in these patients, which the authors attribute to this excess IGF-1 production [45]. Doessing et al demonstrated that subcutaneous GH injections (at dosages between 33.3 and 50 μg/kg/day for 14 days) increased tendon Col-1 expression in healthy human patients 3.9-fold [46].…”
Section: Insulin-like Growth Factormentioning
confidence: 95%